Gender and Generic Clashes in The Years Between (Compton Bennett, 1946) - Nicole Cloarec (Revue LISA)
Because of the enduring success of her novels and her short stories, Daphne Du Maurier is not immediately associated with the theatre except through her father. The Years Between, her first original play, was, however, a popular success. While the play ends up celebrating the Allies’ forthcoming victory, five months before VE Day, what is striking is its very bitter tone as it dramatises the upheaval that society is about to face. This bittersweet note is precisely what singles out its film adaptation when it was released in 1946. The film, however, is very much a product of producer Sidney Box and his wife Muriel, who co-wrote the screenplay. Unlike other Du Maurier’s adaptations, the Boxes do not so much sentimentalize Du Maurier’s work as give it a feminist and socialist agenda, underscoring both the wife’s perspective and the social ramifications of Du Maurier’s drama. In so doing, the film dramatises the gender clashes through subtle disruptions of viewers’ expectations regarding generic conventions.